Kondisi Implementasi Proses Pembelajaran di SMA Kota Padang - Zikri Rahman; Prayitno Prayitno; Mudjiran Mudjiran (Universitas Negeri Padang, 2020)
AbstractThe background of this research is that it is not conducive and the learning process is ineffective and there are still many learning problems experienced by students in schools that cause harm to the students themselves. So study aims to describe the conditions of the implementation of the learning process by the teacher according to students' opinions. The method used in this research is a quantitative descriptive research method, with a population of all students of class X and XI at public high schools and also private high schools accredited A in the city of Padang, where the sample is 137 taken based on purposive sampling technique. The data were obtained by distributing questionnaires and the results were analyzed by calculating the score to determine the percentage and criteria and determining the mean, mode, median and different test (t-test) from the average score of the respondents' answers. The results showed that the conditions for the implementation of the learning process according to the opinions of students at public high schools and private high schools were both in the good category, with an average score of 269.80 and the respondent's level of achievement of 73.91%, where the public high school score was higher than on private high school scores with insignificant differences. This shows that the A-accredited public high school and private high schools in the city of Padang have implemented the principles of high touch and high tech quite well in the learning process.AbstrakLatarbelakang penelitian ini adalah kurang kondusif serta kurang efektifnya proses pembelajaran dan masih banyaknya masalah belajar yang dialami siswa di sekolah yang menyebabkan kerugian bagi siswa itu sendiri. Sehingga penelitian ini bertujuan untuk mendeskripsikan kondisi implementasi proses pembelajaran oleh guru menurut pendapat siswa di SMA Kota Padang. Metode yang digunakan dalam penelitian ini adalah metode penelitia deskriptif kuantitatif, dengan populasi seluruh siswa kelas X dan XI pada SMA Negeri dan juga SMA Swasta yang berakreditasi A di Kota Padang, dimana sampelnya berjumlah 137 yang diambil berdasarkan teknik porpusive sampling. Data diperoleh dengan penyebaran angket dan hasilnya dianalisis dengan menghitung skor untuk menentukan persentase dan kriteria serta menentukan mean, modus, median dan uji beda (t-test) dari skor rata-rata jawaban responden. Hasil penelitian menunjukkan bahwa bentuk kondisi implementasi proses pembelajaran menurut pendapat siswa pada SMA Negeri dan SMA Swasta sama-sama berkategori baik, dengan rata-rata skor sebesar 269,80 dan tingkat capaian responden sebesar 73,91%, dimana skor SMA Negeri lebih tinggi dari pada skor SMA Swasta dengan perbedaan yang tidak signifikan. Hal ini menunjukkan SMA Negeri dan SMA Swasta berakreditasi A di Kota Padang telah menerapkan prinsip-prinsip kewibawaan dan kewiyataan dengan cukup bagus dalam proses pembelajaran.